The potential of Bambara groundnut: An analysis for the People’s Republic of China - Ebrahim Jahanshiri; Ee Von Goh; Eranga M. Wimalasiri; Sayed Azam‐Ali; Sean Mayes; Tengku Adhwa Syaherah Tengku Mohd Suhairi; Nur Marahaini Mohd Nizar; Siti Sarah Mohd Sinin (Food and Energy Security, 2022)
Abstract While China has transformed its economy over recent decades, challenges such as climate change and land degradation have continued to impact its agriculture. These effects along with changes in diets and growing food imports will force China to look for alternative cropping options. Despite the broad potential of Bambara groundnut (Vigna subterranea L. Verdc) as a resilient and nutritious underutilized crop, less is known about its potential in Asia. Here, we explore the potential of Bambara groundnut to become a mainstream crop in mainland China. A suitability analysis is presented for Bambara groundnut to examine the degree of seasonal adaptability of this crop against its climate and soil requirements across China. Results showed that the crop has yield potential in areas that can be too marginal for production of other mainstream crops such as soybean (Glycine max). If realized, the potential of Bambara groundnut could contribute to China's agriculture and reduce its reliance on vegetable protein imports. Using an average seasonal potential yield of 0.85 t/ha over a potential available area of between 55 and 112 million ha (based on 4 land availability scenarios) and modest price of 143 USD/t, yearly income between USD 6 and 13 billion can potentially be contributed by widespread cultivation of this crop. As well as food security, this drought‐resistant nitrogen‐fixing legume could also contribute to land rehabilitation, particularly in the areas where shift in planting dates and land degradation is noticeable. This study demonstrates the need for more investment and research into adoption of Bambara groundnut and other underutilized crops that have the potential to transform agriculture in populous Asian countries.